Vrednotenje ustreznosti mreže vodomernih površinskih vodotokov v Sloveniji - Frantar, Peter (Geografski vestnik, 2003)
Evaluation compares two different methodologies of spatial suitability of the water gauging stations network on surface waters in Slovenia. We involved two main spatial factors that considerably influence the monitoring network: the area of hydrometric hinterland and the stream length in it. We used cabinet approach with help of databases that were processed with GIS analysis in MapInfo and Excel software.
Keywords: hidrogeografija; površinske vode; tekoče vode; vodni režim; rečni režim; merjenje; merilne metode; Slovenia; Slovenija